Within-Day Variability of Pain and Its Relation to Quality of Life in Children with Juvenile Primary Fibromyalgia Syndrome. Issue 3 (2nd October 2015) - Ghaly, Mona Sayed; Handouka, Nesrin M.; Khashana, Abdelmoneim K.; Shalaby, Sherein A.; Fahim, Ayman E.; Ramadan, Ahmed E.
Abstract: Objective: To determine the variability in pain intensity experienced by children with Juvenile Primary Fibromyalgia Syndrome (JPFS) and to relate within-day patterns of pain to children's quality of life. Subjects and methods: Pain intensity was self-reported on a 0–10 cm visual analog scale by 46 young subjects with JPFS using a daily booklet chart three times a day for seven days. Forty-six healthy children and adolescents matched by age and sex were randomly recruited as controls from a pediatric clinic on a voluntary basis. Variability in pain during the day was investigated using a multidimensional pain survey that was completed three times daily in a printed booklet for one week and was related in the primary evaluation to scores for tender points and pediatric quality of life (PedsQL v 4.0). Results: Variations in pain intensity were observed during the day in patients with JPFS. The majority of JPFS patients (67%) had a high Average Absolute Change (AAC) in pain (>1 VAS unit), and a lower quality of life was associated with high pain variability. Conclusions: Pain intensity in JPFS varies throughout the day. Higher pain variability is usually associated with a lower quality of life. Psychological and functional aspects should be addressed with approaches that can support children with JPFS and their family members.